Más condições de vida na infância e na adolescência são fatores de risco para mortalidade precoce? Diferenças de sexo - Souza, Aline Fernanda de (Universidade Federal de São Carlos, 2020)
Background: Adverse early life conditions seem to be associated with negative health outcomes. However, it is not known whether such conditions can contribute to the occurrence of an early death. Aims: Investigate the association between adverse early life conditions and mortality prior to 80 years and whether there are sex differences. Method: 941 participants of the English Longitudinal Study of Ageing who died (before or after 80 years) between 2007 and 2018. At baseline (2006), all participants were evaluated regarding their socioeconomic status, infectious diseases and parental stress in childhood and adolescence. Logistic regression models were created for each sex and adjusted by the socioeconomic, behavioral and clinical variables of the participants in 2006. Results: Living with only one parent (OR = 3.79, 95% CI: 1.35 – 10.67), overprotected by the father (OR = 1.12, 95% CI: 1.01 – 1.25) and having an infectious disease in childhood or adolescence (OR = 2.05, 95% CI: 1.15 – 3.66) were associated with the risk of death prior to 80 years of age among the men. Overprotection by the father (OR = 1.22, 95% CI: 1.07 – 1.39) was a risk factor for death prior to 80 years, whereas a low occupational class of the head of the household (OR = 0.58, 95% CI: 0.34 – 0.98) and high levels of care from the mother in childhood and adolescence (OR = 0.86, 95% CI: 0.76 – 0.99) were protection factors among the women. Conclusions: Worse socioeconomic and health conditions in childhood and adolescence increase the risk of early death among men. Overprotection on the part of the father increases the risk of early death in both sexes, whereas high levels of care from the mother protects women from this situation.
Are adverse early life conditions risk factors for early mortality? Gender differences
Keywords: Condições pregressas de vida; Primeira infância; Estilo parental na infância e adolescência; Sobrevivência; Longevidade; Childhood conditions; Early childhood; Parenting style in childhood; Survival; Longevity; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL